Penerimaan Peserta Didik Baru Berbasis Zonasi di SMA Negeri 1 Sugihan-Banyuasin - Ibrahim Ibrahim; Nadisya Afifah; Septiana Septiana; Mardiah Astuti (Politeknik Kampar, 2023)
This research examines the process of implementing the new Student Acceptance System (PPDB) at SMA Negeri 1 Sugihan in the 2023/2024 academic year. This type of research is qualitative, with a descriptive approach. Data collection methods through interviews, observation and documentation. Data analysis techniques through data reduction, data presentation and data verification. To obtain the validity of the data, this research was carried out through triangulation namely source, time and method. The results of the study show that the process of accepting new students through the zoning system has been carried out properly, by allocating a minimum of 50% of admissions from the zoning system. This system follows the rules of the government and also the regulations of the existing system. Acceptance of the zoning pathway is important to implement to provide a sense of justice for students who are in the closest environment to the school.